A cross-sectional study on dermatology practice in general medicine: specialists’ referral, training needs and teledermatology in Morocco - Ait Oussous, Sara; Chakiri, Radia (Bali Dermatology Venereology and Aesthetic Journal, 2024)
Background: Demographic and geographic constraints make access to specialists difficult, reinforcing the role of general practitioners (GPs) in dermatology. The purpose was to investigate dermatology practice, referral patterns to dermatologists, training needs in this field, and their opinions on teledermatology. Methods: A survey questionnaire was randomly distributed through Google Forms among Moroccan GPs. The statistical analysis of the collected data was carried out using SPSS. Results: 189 responses were collected. The mean age was 41.2 years. 61.4% were female. The proportion of dermatological consultations in general practice was 10 to 20% in 42.9% of cases. Dermatological disorders were the main reason for consultation in 42.9% of cases. Approximately 75.6% of the GPs felt they were moderately or not proficient in dermatology. 64% were not satisfied with their initial training. 84.7% were interested in additional training courses dedicated mainly to inflammatory pathologies (82%), infectious diseases (78.8%), and facial dermatoses (71.4%). 64.6% favored teledermatology and saw it as interesting, mainly for obtaining a rapid diagnostic opinion (71.4%) and training through direct exchange with the specialist (67.7%). A multivariate analysis was performed using age, practice location, and recent continuing education. Conclusion: Our study has highlighted insufficient initial training for current practice and, therefore, a need for further training. This suboptimal diagnostic capacity would contribute to the increase in the dermatologist use by GPs. The development of teledermatology could respond to this problem.